Impact of the COVID-19 pandemic on ongoing health research: an ad hoc survey among investigators in Germany - Christian Apfelbacher; Tanja Bratan; Heike Aichinger; Nicole Brkic; Jana Rueter; Lisa Boyer; Julika Loss (BMJ Open)
Objectives To gain insights into the impact of the COVID-19 pandemic on ongoing health research projects, using projects from a selected funding programme in Germany as an example.Design Online survey and validation workshop.Setting Lockdowns and social distancing policies impact on clinical and public health research in various forms, especially if unrelated to COVID-19. Research institutions have reduced onsite activities, data are often collected remotely, and during the height of the crisis, clinical researchers were partially forced to abandon their projects in favour of front-line care.Participants survey 120 investigators of health research projects across Germany, performed between 15 and 25 May 2020; workshop: 32 investigators, performed on 28 May 2020.Results The response rate (78%) showed that the survey generated significant interest among investigators. 85 responses were included for analysis, and the majority of investigators (93%) reported that their projects were affected by the pandemic, with many (80%) stating that data collection was not possible as planned, and they could not carry out interventions as intended (67%). Other impacts were caused by staff being unavailable, for example, through child or elder care commitments or because of COVID-19 quarantine or illness. Investigators also reported that publications were delayed or not feasible at all (56%), and some experienced problems with PhD or Masters theses (18%). The majority of investigators had mitigation strategies in place such as adjustment of data collection methods using digital tools (46%) or of project implementation in general (46%), others made changes in research design or research questions (27%).Conclusions The COVID-19 pandemic has severely impacted on health research projects. The main challenge is now to mitigate negative effects and to improve long-term resilience in health research. The pandemic has also acted as a driver of innovation and change, for example, by accelerating the use of digital methods.